A Review Paper on Correction Methods for Solar Irradiances Data - Suzan Katamoura , Layla Hajar, Mehmet SabihAksoy (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
There is big data related to solar resources and associated weather parameters that are actively collected from more than 45 solar radiation measurement stations operating around Saudi Arabia. King Abdullah City for Atomic and Renewable Energy (K.A.CARE) has been managing this data since 2013 and making it available through Renewable Resources Atlas Portal. This data uses to support stakeholders in decision-making related to renewable energy projects in Saudi Arabia. However, maintaining such a large-scale network of measurement devices and receiving streaming data every minute over the years might result in some data issues in certain periods. These issues can result from different reasons. In this case, the data was slightly affected while maintaining the sensors of measurement devices, particularly the physical cleaning schedule. This paper aims to review available solar data correction methods in the literature to solve these instances and correct data values. The goal is to investigate the different techniques and find the most applicable to implement on K.A.CARE data.